Leveraging the Electronic Medical Record to Identify Predictors of Nonattendance to a Diabetes Self-Management Education and Support Program. Issue 5 (October 2019) - Bzowyckyj, Andrew S.; Aquilante, Christina L.; Cheng, An-Lin; Drees, Betty
Purpose: The purpose of this study is to identify patient-specific factors, easily obtainable from the electronic medical record (EMR), that are associated with nonattendance to a group Diabetes Self-Management Education and Support (DSMES) program among an adult population with type 2 diabetes. Methods: This study used a retrospective cohort design, with attendance to a group DSMES session as the primary outcome. The study included adult patients with diagnosed type 2 diabetes who were scheduled for a group DSMES session between March 1, 2013, and June 30, 2017. Patients who were pregnant or who had other types of diabetes (eg, type 1 diabetes, prediabetes, gestational diabetes) were excluded. Results: A higher A1C, required copay for DSMES, low socioeconomic status, increased number of diabetes medications prescribed, the presence of a prescription for any insulin, and a higher calculated total daily dose of insulin were all associated with a decreased likelihood of attendance. Only older age was associated with an increased likelihood of attendance. Conclusion: Using the EMR to identify patients who need more intensive intervention strategies can help programs direct resources to those who need them most. Having identified these at-risk individuals, a targeted communication and outreach strategy can be developed to assist these individuals with overcoming barriers to attending DSMES.